The Validity of the Instrument to Evaluate Social Network in the Ageing Population: The Collaborative Research on Ageing in Europe Social Network Index. (12th August 2013) - Zawisza, Katarzyna; Galas, Aleksander; Tobiasz‐Adamczyk, Beata; Chatterji, Somnath; Haro, Josep Maria; Miret, Marta; Koskinen, Seppo; Power, Mick; Leonardi, Matilde; Leonardi, Matilde; Quintas, Rui; Raggi, Alberto
<x xml:space="preserve">Abstract</x> The aim of the study was to create a simplified, easy implementable multidimensional instrument to assess all relevant elements of the structure and function of social network within individuals across different European countries and to provide the tool for health professionals and policy makers. The analysis was based on the sample of 10 446 non‐institutionalized adult population from Finland, Poland and Spain. The Social Network Questionnaire Collaborative Research on Ageing in Europe Social Network Index (COURAGE‐SNI) was part of the COURAGE questionnaire. The indicators of the functioning of social network ties (close relations), frequency of direct contact and general support were evaluated. Functions were assess within the main structural components as spouse, parents, children, grandchildren, other relatives, friends, coworkers and neighbours. The exploratory factor analysis revealed five main latent components of social network with one component composed of hierarchical part. The confirmatory factor analysis provided an acceptable fit for the model. The generalize partial credit model was used to calculate factor scores for five components of the COURAGE‐SNI considering the social networks of 'spouse/partner', 'parents', 'other family members', 'neighbours' and 'friends and co‐workers'. The scores for every component were recalculated so as to provide the social network saturation ranged from 0 (the lowest) to 100% (the highest possible). Finally, the COURAGE‐SNI score was obtained as the sum of weighted information calculated by the item response theory procedure for every aforementioned component. In summary, the COURAGE‐SNI showed good reliability and content validity and seems to be a promising tool for the assessment of the social network phenomenon across European countries. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Message The Courage‐SNI is a new tool to assess the construct of social network in population studies. The Courage‐SNI is an instrument useful to identify high risk groups or populations whose social network is poorer.